Simuliidae da Amazônia IV1) Descrição de Simulium fulvinotum sp. n. (Diptera Nematocera) - Cerqueira, Nelson L.; Melo, J. A Nunes de (Amazoniana, 1968)
The authors give the description of the female, male, pupa and larva of Simulium Fulvinotum sp. n. from laboratory-grown material collected at Igarapé do Tarumã and Igarapé do Gigante, at Ponta Negra, in the outskirts of Manaus, associated with larvae and pupae of Simulium amazonicum GOELDI 1905 and Simulium goeldii CERQUEIRA E NUNES DE MELO,1966. They discuss the similarity between it and Simulium LUTZ, 1910 and Simulium rorotaense FLOCH et ABONNENG ,1946 from which it is separated by very distinct characteristics observed in the adults, pupae and larvae. They draw attention to the fact that adults have never been found attacking humans or other animals during field investigations. during field investigations.
Keywords: Simulium Fulvinotum sp. n